Digital elevation model "Ville" from 1893 - Henselowsky, Felix; Rölkens, Julian; Kelterbaum, Daniel; Bubenzer, Olaf (Universität, 2021)
The area of the Ville in western Germany is of particular importance for studying anthropogenic induced relief changes, as it belongs to the largest and oldest historic lignite mining areas worldwide. Comparison of topographic data from the first geodetic mapping in 1893 to 2015 allows the quantification of relief changes in a completed example of a post-mining landscape. The dataset "Digital Elevation Model "Ville" from 1893" is computed based on the digitized contour lines of the historic map Preußische Neuaufnahme, which is the first geodetic mapping in the area. The DEM has a spatial resolution of 30 m. ...